2001
DOI: 10.1111/j.0006-341x.2001.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Capture-Recapture, Epidemiology, and List Mismatches: Several Lists

Abstract: In applying capture-recapture methods for closed populations to epidemiology, e.g., in the estimation of the size of a diabetes population, one comes up against the problem of list errors due to mistyping or misinformation. This problem has been studied for just two lists by Seber, Huakau, and Simmons (2000, Biometrics 56, 1227 1232) using the concept of tag loss borrowed from animal population studies. In this article, we discuss a similar method that can be extended to an arbitrary number of lists. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…by Seber and Felton [25]. Their technique has recently been generalized to apply to problems in human epidemiology by Seber et al [26], Lee et al [27] and Lee [28]. While our methods are probabilistic, we assume complete and accurate information in the x vector.…”
Section: Discussionmentioning
confidence: 99%
“…by Seber and Felton [25]. Their technique has recently been generalized to apply to problems in human epidemiology by Seber et al [26], Lee et al [27] and Lee [28]. While our methods are probabilistic, we assume complete and accurate information in the x vector.…”
Section: Discussionmentioning
confidence: 99%
“…The ecology literature has developed some solutions to imperfect matching, which frame the problem in terms of lost tags on captured animals [Lee et al, 2001]. Similarly, the public health literature includes examples of capture-recapture estimates for cases when Cadwell et al, 2005].…”
Section: Multiple Systems Estimationmentioning
confidence: 99%
“…If we retain the data partitions, we would also like to compare the affect of increasing (or decreasing) the number of zero cells allowed in a "valid" dataset combination. We would also like to explore ways to incorporate uncertainties in our record matching into our models and the potential applicability of 'lost-tag' research in ecology [Lee et al, 2001] and insufficient identifying markers in public health [Laska et al, 2003, Cadwell et al, 2005. Lastly, we are eager to apply this new method in other departments and, eventually, across all of Colombia.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This may occur if the data consist of incomplete summary statistics or if individuals are misidentified on some occasions. Examples of capture-recapture studies that are prone to identification errors include (i) multi-list studies in which individuals may be matched based on personal information such as name, birth date, medical record number (Seber, Huakau, and Simmons, 2000;Lee et al, 2001;Sutherland and Schwarz, 2005;Fienberg and Manrique-Vallier, 2009), (ii) animal studies in which individual identity is found from noninvasive sampling, for example, genetic information from scat or hair (Wright et al, 2009;Link et al, 2010;Yoshizaki et al, 2011) or photographic ID of individuals (Yoshizaki et al, 2009;Bonner and Holmberg, 2013;McClintock et al, 2013), and (iii) studies in which (at least) two sources of capturerecapture information are available for the same population with little to no information about how the individual IDs in one source corresponds to individual ID from the other sources (Bonner and Holmberg, 2013;McClintock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%